More Than DNA Methylation: Does Pleiotropy Drive the Complex Pattern of Evolution of Dnmt1? - Amukamara, Ashley U.; Washington, Joshua T.; Sanchez, Zachary; McKinney, Elizabeth C.; Moore, Allen J.; Schmitz, Robert J.; Moore, Patricia J. (Frontiers in Ecology and Evolution, 2020)
DNA methylation is an important chromatin modification that can stably alter gene expression in cells and maintain genome integrity in plants and vertebrates. The function of DNA methylation outside of these well-studied systems, however, is unclear. Insects, in particular, represent an understudied group. Variation in the level of DNA methylation and gains and losses in the maintenance methyltransferase, DNMT1, across the insect tree of life suggests that there is much we don’t understand about DMNT1 function and evolution. One constant across the studies examining patterns of Dnmt1 expression in insects is that expression is consistently high in reproductive tissues compared to somatic tissue. The explanation for this has been that DNMT1 is required in tissues that have high levels of cell division. Our previous study found that downregulation of Dnmt1 expression in the milkweed bug Oncopeltus fasciatus results in the expected reduction of DNA methylation, no global changes in gene expression reflecting changes in DNA methylation, and the loss of the ability to produce viable oocytes. Here, we show that females treated with ds-Dnmt1 RNA during larval development have a more extreme phenotype; they lack oocytes entirely but develop a normal somatic ovary. Our results indicate a specific role for DNMT1 in the formation of gametes and are consistent with data from other systems, including Tribolium castaneum, a species does not have DNA methylation. We propose that DNMT1 has multiple functional roles in addition to methylating DNA, which explains its complex patterns of evolution.